Chimeric antigen receptor (CAR) T-cell therapy in hematologic malignancies: clinical implications and limitations - Blüm, Philipp; Kayser, Sabine (Cancers, 2024)
Chimeric antigen receptor (CAR) T-cell therapy has become a powerful treatment option in B-cell and plasma cell malignancies, and many patients have benefited from its use. To date, six CAR T-cell products have been approved by the FDA and EMA, and many more are being developed and investigated in clinical trials. The whole field of adoptive cell transfer has experienced an unbelievable development process, and we are now at the edge of a new era of immune therapies that will have its impact beyond hematologic malignancies. Areas of interest are, e.g., solid oncology, autoimmune diseases, infectious diseases, and others. Although much has been achieved so far, there is still a huge effort needed to overcome significant challenges and difficulties. We are witnessing a rapid expansion of knowledge, induced by new biomedical technologies and CAR designs. The era of CAR T-cell therapy has just begun, and new products will widen the therapeutic landscape in the future. This review provides a comprehensive overview of the clinical applications of CAR T-cells, focusing on the approved products and emphasizing their benefits but also indicating limitations and challenges.